Corrosion behavior of titanium wires: An in vitro study - Thakur Prasad Chaturvedi; Ram Sagar Dubey (Wolters Kluwer Medknow Publications, 2012)
Context: Teeth and restorations are subjected continuously to degradation in hostile physical and chemical environments, resulting in corrosion. Component of liquid or solid is an important factor influencing the corrosion of metallic appliances placed in the oral cavity. Aims: To study in vitro corrosion of titanium wires immersed in solutions of toothpaste and chocolate in artificial saliva. Materials and Methods: Immersion test and electrochemical studies using different parameters, including corrosion potential (E corr ), cathodic Tafel constant (βc), anodic Tafel constant (βa), corrosion current (I corr ), polarization resistance (R p ), and corrosion rate of titanium wires, were done in solutions of artificial saliva containing Colgate™ toothpaste and Amul™ chocolate. Photomicrographs were also taken. Results: The results showed degradation of titanium wires by electrochemical attack when they were placed in the hostile electrolytic environments provided in the experiments. Surface analysis of titanium wires showed pitting and localized attacks on the surface. Pitting corrosion was found in the titanium wires.